Postgraduate students'perceptions of their supervisors' mentoring skills (Gaziosmanpasa University example) - Arabaci, I. Bakir; Ersozlu, Alpay (Elsevier Science Bv, 2010)
The aim of this study is to identify postgraduate students' perceptions of their supervisors' mentoring skills. The sample comprises 70 postgraduate students at the Institute of Science and the Institute of Social Sciences at Gaziosmanpasa University. Data collecting tools were designed and their validity and reliability were affirmed. The results suggest that students have positive image of their supervisors' mentoring skills. The students' sex, the institute they study at, their levels of postgraduate study, their supervisors' ages and academic status, seniority and whether they obtained their doctoral degrees in Turkey or abroad make a significant difference on the students' perceptions of their supervisors' mentoring skills. (C) 2010 Elsevier Ltd. All rights reserved.
2nd World Conference on Educational Sciences (WCES-2010) -- FEB 04-08, 2010 -- Bahceschir Univ, Istanbul, TURKEY
Keywords: Postgraduate study; supervisor; mentor; mentoring skills; student perceptions